2012
DOI: 10.1080/00224499.2011.589101
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Positive and Negative Consequences of Sex Based on Daily Reports Among College Students

Abstract: Because sexual behavior may be associated with a broader range of outcomes than physical consequences like sexually transmitted infections and pregnancy, it is important to understand consequences of sex that may influence mental and social well-being in emerging adulthood. This article describes the short-term intrapersonal and interpersonal consequences reported by college students on days they engage in vaginal sex and what factors predict experiencing particular consequences. Data are from first-year colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 37 publications
2
68
0
Order By: Relevance
“…In one study, 81% of undergraduate participants reported engaging in hookups, with 34% engaging in sexual intercourse (Reiber & Garcia, 2010). Although casual sex and other varieties of hookups may be viewed as culturally normative in emerging adulthood, they come with a host of negative consequences including sexual assaults, unintended pregnancies, and sexually transmitted infections (Chesson et al, 2003;Corbin & Fromme, 2002;Garcia et al, 2012;Perkins, 2002;Vasilenko et al, 2012). Given that emerging adulthood is characterized by increased involvement in romantic and sexual relationships as well as heavier drinking, it is not surprising that these risk behaviors are significantly correlated at the global level (for a review, see Cooper, 2006; for a meta-analytic review, see Claxton et al, 2015).…”
Section: Abstract Objectivementioning
confidence: 99%
“…In one study, 81% of undergraduate participants reported engaging in hookups, with 34% engaging in sexual intercourse (Reiber & Garcia, 2010). Although casual sex and other varieties of hookups may be viewed as culturally normative in emerging adulthood, they come with a host of negative consequences including sexual assaults, unintended pregnancies, and sexually transmitted infections (Chesson et al, 2003;Corbin & Fromme, 2002;Garcia et al, 2012;Perkins, 2002;Vasilenko et al, 2012). Given that emerging adulthood is characterized by increased involvement in romantic and sexual relationships as well as heavier drinking, it is not surprising that these risk behaviors are significantly correlated at the global level (for a review, see Cooper, 2006; for a meta-analytic review, see Claxton et al, 2015).…”
Section: Abstract Objectivementioning
confidence: 99%
“…In addition to the mental health impact, commonly cited adverse effects include unintended/ unwanted pregnancy, sexually transmitted infections, including HIV/AIDS, and sexual victimization (Claxton and van Dulmen 2013;Heldman and Wade 2010;Vasilenko et al 2012). For those who have casual sex, in addition to potentially experiencing an adverse health effect, there is the added burden of worrying about these negative health effects.…”
Section: Casual Sex and Sexual Healthmentioning
confidence: 99%
“…For those who have casual sex, in addition to potentially experiencing an adverse health effect, there is the added burden of worrying about these negative health effects. For example, Vasilenko et al (2012) found that female college students had almost three times greater odds of worrying about their health when they had sex with an uncommitted partner as compared to a dating partner. This kind of worrying likely results in negative perceptions that probably reduces the possible positive affect of sexual encounters.…”
Section: Casual Sex and Sexual Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Such findings are echoed in emerging adults, among whom sexual enjoyment and sexual satisfaction are linked to higher quality daily interpersonal interactions, increased autonomy and improved empathy. 14,15 Similar work in adolescents, however, is mixed -some studies suggest that sexuality, sexual experience and relationships are associated with both higher and lower levels of health and well-being, while other studies show no relationship. [16][17][18] One explanation for this conflicting set of findings among adolescents is that most studies only examine the impact of one or two single sexual health indicators rather than a full set of healthy sexual development measures, as predictors of health.…”
Section: Introductionmentioning
confidence: 99%